Simulation of primary particle size distributions in a premixed ethylene stagnation flame - Hou, Dingyu (2021)
Numerical simulation of soot formation in a laminar premixed burner-stabilized ethylene stagnation flame was performed with a detailed population balance model (DPBM) capable of tracking full structural details of aggregates as well as their chemical composition. A thorough parametric sensitivity study was carried out to understand the influence of individual sooting processes on the computed primary particle size distributions (PPSDs). The rate of production of pyrene, coagulation efficiency and surface growth rate were found to have significant effects on the computed PPSDs. Besides, we found that the instantaneous sintering between small primary particles (PP) can affect the computed PPSDs drastically while sintering between large PPs within aggregates only had mild effects. For an ethylene premixed flame with stagnation plate height being 1.2 cm (Combust. Flame, 198:428-435, 2018), good agreement was obtained between both the computed and measured PPSD and fractal dimension, which supports the current mechanisms contributing to the evolution of PPs, i.e. nucleation, coagulation, surface growth and sintering. Moreover, time scale analysis for individual sooting processes was performed to determine the dominant particle processes at different periods of time, which helped explain the evolution of soot morphology.